2003
DOI: 10.1039/b307217g
|View full text |Cite
|
Sign up to set email alerts
|

On the water promoted reaction of titanium isopropoxide with carbon dioxideElectronic supplementary information (ESI) available: experimental details. See http://www.rsc.org/suppdata/cc/b3/b307217g/

Abstract: Insertion of carbon dioxide into titanium isopropoxide takes place only in the presence of trace quantities of water to give an isopropyl carbonato cluster which has been crystallographically characterised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…It is also known that the insertion reaction of carbon dioxide with titanium(IV) isopropoxide takes place only in the presence of one fourth equivalents of water [12]. In this study it has been found that the imine never undergoes insertion into the Ti-O bond.…”
Section: Metathesis Reaction Catalyzed By Group(iv) Metal Alkoxidesmentioning
confidence: 86%
“…It is also known that the insertion reaction of carbon dioxide with titanium(IV) isopropoxide takes place only in the presence of one fourth equivalents of water [12]. In this study it has been found that the imine never undergoes insertion into the Ti-O bond.…”
Section: Metathesis Reaction Catalyzed By Group(iv) Metal Alkoxidesmentioning
confidence: 86%
“…The linkage between the octahedra shows variations; the main difference between the cluster types is the ratio between shared vertices and edges. The titanium atoms are connected by μ 2 -oxo and μ 3 -oxo bridges {μ 4 -oxo in [Ti 4 O 2 (OiPr) 10 (OOCR) 2 ] [15,51] }. The presence of at least one μ 3 -oxo bridge in these structures enables most of the carboxylate-substituted Ti-oxo clusters to be described as substructures of the cubic [Ti 4 O 4 ] motif.…”
Section: Introductionmentioning
confidence: 99%
“…The plane of the phenyl ring was found to be 36°with respect to the plane containing the Ti-N-C-O. In an analogous reaction of carbon dioxide, it was recently found that the carbonate prefers a bridging mode [20]. Carboxylate groups also prefer to have a bridging mode [21].…”
Section: Resultsmentioning
confidence: 96%